1999
DOI: 10.1002/(sici)1099-0488(19990601)37:11<1155::aid-polb10>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and mechanical properties correlations of PA6/PPO blends compatibilized with SMA

Abstract: The effects of the compatibilizer, styrene maleic anhydride (SMA‐8% MA) upon the change of morphology and molecular dynamics of polyamide‐6 (PA6) and poly (2,6‐dimethyl‐1,4‐phenylene oxide) (PPO) blends were investigated by means of solid‐state NMR techniques. With increasing amounts of SMA, the domains correspond to PA6 and PPO are reduced and the polymer segmental mobility increased. The correlation between NMR relaxation time, T italicH1ρ, and the bulk mechanical properties provide a molecular level underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…During the last decade, extensive research has been carried out in areas of compatibilization of the nylon/ PPO blends [11][12][13][14][15][16][17][18]. Blends of a PPO/PA6 alloy toughened with a novel polyolefin elastomer, poly(ethylene-1-octene) (POE), were prepared via melt extrusion [6].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, extensive research has been carried out in areas of compatibilization of the nylon/ PPO blends [11][12][13][14][15][16][17][18]. Blends of a PPO/PA6 alloy toughened with a novel polyolefin elastomer, poly(ethylene-1-octene) (POE), were prepared via melt extrusion [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, at lower concentrations, there is a strong interaction between the polymer and clay particles, resulting in effective stress transfer from the PBAT matrix to MMT and HNT. Furthermore, the addition of clays enhances the crystallinity degree of PBAT, which impacts the tensile strength of the films as crystalline regions act as mechanical reinforcement 42 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the addition of clays enhances the crystallinity degree of PBAT, which impacts the tensile strength of the films as crystalline regions act as mechanical reinforcement. 42 From Figure 6 it is observed that the elongation at break of pure PBAT is 309% and 475% in the machine and transverse direction, respectively. Typically, the addition of reinforcing particles leads to a decrease in this property of plastic films.…”
Section: Mechanical Properties Of Composite Filmsmentioning
confidence: 98%
“…Dedecker and Groeninckk5 also used SMA (8 wt % MA) as a compatibilizer for PPO/PA and studied the reactions between PA6 and SMA. Chu et al14 studied the correlation between the molecular dynamics and mechanical properties of PPO/PA compatibilized by SMA (8 wt % MA). The addition of SMA reduced the size of dispersed phase (PA) and increased the interfacial contact area, leading to the increase in the tensile strength and unnotched impact strength 14…”
Section: Introductionmentioning
confidence: 99%